2013
DOI: 10.1016/j.hemonc.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells promote leukaemic cells aberrant phenotype from B-cell acute lymphoblastic leukaemia

Abstract: Lymphoid cell maintenance, at early stages of differentiation, was significantly promoted by BM-MSC in normal and leukaemic cells. Co-cultures also modulated the expression of antigens associated with the B-ALL asynchronous phenotype as CD10 co-expressed with CD19 and CD20. To our knowledge, this is the first time that CD10, CD19 and CD20 leukaemic antigens have been reported as being regulated by BM-MSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…To obtain MSC, bone marrow (BM) samples were obtained with the support of the Department of Orthopedics and Traumatology of Hospital Universitario San Ignacio (Bogota, Colombia) from volunteer donors (undergoing hip replacement surgery) after signing the informed consent form approved by the Hospital Ethics Committee. BM-MSC were isolated and cultured as previously published (14, 15), and they were used in passages 3–5 for a 3D culture system. The BM-MSC phenotype was assessed by flow cytometry with a FACS Aria-II cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain MSC, bone marrow (BM) samples were obtained with the support of the Department of Orthopedics and Traumatology of Hospital Universitario San Ignacio (Bogota, Colombia) from volunteer donors (undergoing hip replacement surgery) after signing the informed consent form approved by the Hospital Ethics Committee. BM-MSC were isolated and cultured as previously published (14, 15), and they were used in passages 3–5 for a 3D culture system. The BM-MSC phenotype was assessed by flow cytometry with a FACS Aria-II cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…These cells, which express common mesenchymal antigens such as CD73 and CD105 or particular antigens (according to the subtype) such as CD146, CXCL-12 (CAR cells), nestin and leptin receptor (LepR), have in common the secretion of two determining soluble factors for HSC: CXCL-12 (SDF-1) and SCF (11, 12), which participate in maintaining the viability, self-renewal and mobilization of hematopoietic cells. Some MSC populations of the vascular niche are more resistant to chemotherapy and induce the regeneration of HSC after exposure to cytotoxic agents (13), and in vitro, they can maintain the phenotypic and functional characteristics of HSC of umbilical cord blood and leukemic cells (14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are known for its ability as immune modulator capable of regulating proliferation and differentiation of immune cells such as macrophages, B and T cells, NK cells, and even mast cells [ 30 ]. Studies suggested that MSCs promote cellular proliferation and maintenance of either normal or malignant hematopoietic cells in direct co-culture [ 31 , 32 ]. Our results indicated TRAIL secretion by ADMSCs induced cellular inhibition of hematopoietic malignant cell noticed in REH line shown by Figure 4 B.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical cluster analysis of these surface markers shows that, after co-culture with MSCs, an association between pre-pre-B-cells from control patients (Ct) and B-ALLBMMNCs gradually forms. However, no association between these cell groups has been observed after their co-culture in the absence of BMMSCs [ 51 ].…”
Section: Characterization Of Msc-b Cells Interactionsmentioning
confidence: 99%